Konsep Dasar Psikologi Pendidikan - Cici May Linda; Muhimatus Shofiyani; Prihaten Maskhuliah (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
Educational psychology is a branch of psychology that studies individual behavior and mental processes in the context of education. This article discusses the essence of psychology, including definitions, objects of study, and the role of psychology in learning. Educational psychology is dynamic and encompasses behavioral changes that occur due to the learning process, both through individual growth and development as well as interactions within the educational environment. Through an empirical approach, educational psychology seeks to understand how teaching methods and learning experiences can influence learning outcomes and the development of positive attitudes among students. Thus, educational psychology contributes to the improvement of educational quality and individual development within society.